Corruption dynamics : the golden goose effect - Niehaus, Paul (2013)
Argues that if there is some chance of detecting and dismissing corrupt agents then the principal can mitigate the problem by paying an efficiency wage. Focuses on the dynamic trade-off between extracting rents today and improving one's chances of surviving to extract rent tomorrow, the golden goose effect.